MODIFICATION OF COBALT-METAL ORGANIC FRAMEWORK (Co-MOF) WITH GRAPHENE (Gr) BY SOLVOTHERMAL METHOD AS NON-ENZYMATIC GLUCOSE SENSOR - Yuniasari, Rizki
Early detection is an important step in the spread of disease. Sensor offers a more simple, fast and accurate disease detection method compared to the conventional laboratory methods that are commonly performed. In this study, Cobalt-Metal Organic Framework (Co-MOF) was composited with graphene and used as a sensor for detecting diabetes with electrochemical principles. The selection of Co-MOF material based on its porous nature, large surface area, and good electrochemical properties. Graphene is used for its high conductivity to increase the electrochemical sensor current.